Marine natural products as source of new drugs: a patent review (2015–2018). (3rd April 2019) - Shinde, Pravin; Banerjee, Paromita; Mandhare, Anita
ABSTRACT: Introduction : Natural products from plants, animals, microbes, and minerals have long been a traditional source for the treatment of human diseases. In the past decades, research on natural products for the pharmaceutical industry had declined due to numerous challenges. However, the recent developments in analytical technology, spectroscopy, and high-throughput screening have tremendously revived natural product drug discovery, including contribution from marine-based drugs. The marine environment is a unique resource enclosing a massive biological diversity, which if genuinely explored might potentially lead to breakthrough therapies. A growing number of compounds from marine sources are entering clinical trials and thus, the impact of this field on the pharmaceutical industry is increasing. Areas covered : This review summarizes the progress in the field of marine natural products as therapeutic agents based on an analysis of the patents published in the period January 2015 through June 2018. Expert opinion : Marine organisms are excellent producers of natural chemicals with diverse structures and pharmacological activities. Cumulative increase in the number of patents published in the last few years clearly justifies the importance of these chemicals as sources of new therapeutic agents and this study. Despite the critical supply challenges, marine-derived actives are being explored as sources for anticancer, antimicrobial, antiviral and anti-inflammatory drugs and treatments for several other conditions.